Analisis Konsep Transit Oriented Development (TOD) Di Kawasan Stasiun Tugu Yogyakarta - Faizal, Ar Rofiqi Mohamad; Rahmawati, Ainun (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
The concept of Transit Oriented Development (TOD) is an urban planning approach that emphasizes the integration of public transportation and land use to create sustainable, efficient, and pedestrian-friendly urban areas. This study aims to analyze the level of conformity in the implementation of the TOD concept in the Tugu Station area of Yogyakarta. The data collection methods employed include direct observation and documentation, while the analytical method adopts TOD indicators based on guidelines from ITDP (2017), the Florida TOD Guidebook (2012), and the Indonesian Ministry of Agrarian Affairs Regulation No. 16 of 2017. The assessment of conformity was carried out by measuring variables such as building density, land-use mix, pedestrian network quality, and integration of transportation modes. The results indicate that certain aspects of the area meet TOD criteria, such as the availability of pedestrian pathways and diversity in land use functions. However, deficiencies were also identified in parameters such as pedestrian connectivity, area density, and infrastructure for non-motorized transport. The TOD evaluation score for the Tugu Station area in Yogyakarta was found to be 40.1%, which falls into the bronze standard category, indicating that TOD development in the area is still at an early stage. Although efforts have been made to provide access to public transportation, further improvements are required to meet higher standards, particularly in the indicators of density, land-use mix, walkability, and cycling infrastructure. This research is expected to serve as a reference for transit-oriented area development in other Indonesian cities facing similar challenges in integrating transportation and land use.